Hospitalitas Abimelekh dan Peringatan Allah: Analisis Naratif Kejadian 20:1-18 dan Relevansinya Terhadap Peringatan yang Disertai Kekerasan - Sumiati; Patandianan, Cindy; Rumbi, Frans Paillin (Sekolah Tinggi Teologi Sriwijaya, 2022)
Abstract: This paper aims to examine the story of Abimelech and God by using narrative interpretation as a model approach to answer the question of how is the hospitality shown by Abimelech? Does a good host deserve a warning for the fault of the guest's carelessness? Does the host need to resort to violence against a stranger who harms him? From this article, we will explore what is the background of God's stern warning to Abimelech through dreams. The approach used is the approach approach. The results of the study show that God Abimelech strictly when he was not married Sarah was already married, namely (1) the possibility of Abimelech from the danger of committing sins. (2) the punishment, preventing